2012
DOI: 10.1501/vetfak_0000002531
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alternative cryopreservation procedures on bull semen

Abstract: Summary:The aim of this study was to assess the use of -152°C ultra freezer for freezing and storing bull semen as an alternative to freezing over the liquid nitrogen vapor and storing in liquid nitrogen in terms of certain post-thaw spermatological parameters. Two ejaculates, one per each bull, were used without pooling. Four different freezing and storing protocols were tested. At 1 week, 2 months and 6 months after cryopreservation, the frozen semen was thawed and the seminal parameters were determined. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Inflammatory cytokines secreted by the immune system play a key role in preventing against bacterial or viral infectious diseases and balancing the immune homeostasis (49). The pro-inflammatory cytokines (IL-6, TNF-α) and anti-inflammatory cytokines (IL-10, TGF-β) are key inflammatory cytokines that endorse cellmediated immunity and regulate cytokine secretion homeostasis (50,51). Many documents reported that probiotics could modulate host immune function (52,53) and have been widely used in animal and human in order to enhance the disease resistance capacity (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines secreted by the immune system play a key role in preventing against bacterial or viral infectious diseases and balancing the immune homeostasis (49). The pro-inflammatory cytokines (IL-6, TNF-α) and anti-inflammatory cytokines (IL-10, TGF-β) are key inflammatory cytokines that endorse cellmediated immunity and regulate cytokine secretion homeostasis (50,51). Many documents reported that probiotics could modulate host immune function (52,53) and have been widely used in animal and human in order to enhance the disease resistance capacity (54,55).…”
Section: Discussionmentioning
confidence: 99%